2005
DOI: 10.1080/17453670510041754
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of operatively treated type-C injuries of the pelvic ring

Abstract: Background Internal fixation has become the preferred treatment for type-C pelvic ring injuries, but controversies persist regarding surgical approach and surgical technique.Patients We evaluated 101 consecutive patients with type C1-C3 pelvic ring injuries who had been treated with standardized reduction and internal fixation techniques.Results Our findings suggest a correlation between excellent reduction followed by sufficient fixation of the pelvic ring and functional outcome. Unsatisfactory reduction (dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
86
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 44 publications
(67 reference statements)
13
86
1
2
Order By: Relevance
“…This is in line with the functional outcome reported after SI screw fixation. Lindahl and Hirvensalo reported 83% of patients having excellent or good results following SI screw fixation [13], and Cole et al reported 70.6% of patients with none or only minor functional deficits [5]. As reported by Lindahl and Hirvensalo, post-traumatic pain appeared to be the main driver for the majority of fair results, which accords with our patient population [13].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This is in line with the functional outcome reported after SI screw fixation. Lindahl and Hirvensalo reported 83% of patients having excellent or good results following SI screw fixation [13], and Cole et al reported 70.6% of patients with none or only minor functional deficits [5]. As reported by Lindahl and Hirvensalo, post-traumatic pain appeared to be the main driver for the majority of fair results, which accords with our patient population [13].…”
Section: Discussionsupporting
confidence: 80%
“…Lindahl and Hirvensalo reported excellent/good radiological results in 90% of patients managed with SI screw fixation [13]. Seventy-two percent of our patients returned to their previous work without restrictions, 14.3% were handicapped at work and 14.3% had not returned to work upon follow-up.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Similarly, Denis et al [2] declared that the residual neurological deficit is critical factor affecting the functional outcome. Lindahl and Hirvensalo [19] documented the permanent neurological injury as a strong prognostic factor. Roy-Camille type III injuries had significantly worse outcome in this series.…”
Section: Discussionmentioning
confidence: 99%
“…LC1 represents a broad spectrum of injury, including within the same category minimal ''buckle'' impaction fractures of the anterior sacrum to comminuted sacral fractures that extend to and through the posterior cortex [14]. There is general agreement that fractures displaced more than 1 cm benefit from surgical stabilization, but it is unclear if LC1 and LC2 fractures that are minimally displaced on radiographs obtained shortly after injury benefit from surgical intervention [7,16,20].…”
Section: Introductionmentioning
confidence: 99%